Correlation of neuropsychological indicators of child development with speech: empirical research underpinning the National Children’s Health Prevention Program - Otašević, Jadranka; Vukašinović Radojičić, Zorica; Otašević, Božidar (Vojnosanitetski pregled, 2022)
Background/Aim. Psychophysiological disorders and speech pathology is one of the priority public health problems in the Republic of Serbia. A child’s growth and development proceed in a particular sequence and course, depending on individual physiological capacities, quality of neuromuscular structures, and stimuli, which can be significantly affected by the environment. The development of speech from birth to the adult age is a result of the interaction of neurocognitive factors that contribute to the gradual attainment of phonological presentation and motor control abilities. The aim of the study was to examine the connection between manipulative manual dexterity, oral praxis, and lateralization with the development and speech in children and their potential for the development of prevention programs. Methods. The sample included 60 children from Belgrade of both sexes, aged between 5.5 and 7 years. Of these, 30 made up the experimental group – children with deviations in speech development (articulation disorders), and 30 made up the control group – typically developing children from the general population. The instruments used were the Manipulative Manual Dexterity Test (Lafayette), Oral Praxis Test, and part of the Test for assessing lateralization (auditory, visual, and functional). Results. The hand grip development level was statistically significantly different between the experimental and the control group (χ2 = 21.40, df = 3, p < 0.01). The presence of associated involuntary movements statistically significantly differed between the experimental and the control group examinees (χ2 = 10.58, df = 1, p < 0.01). Oral praxis statistically significantly differed between the experimental and the control group (t = 2.01, p < 0.05). Visual laterality statistically significantly differed (χ2 = 7.56, p < 0.05) between the observed groups. When all predictors were taken into account, significant contribution to the explanation of the existence of speech pathology (articulation disorders) was given by the variables: Visual lateralization [odd ratio (OR) = 0.38; 95% confidence interval (CI) = 0.179–0.832; p = 0.015] and the level of hand grip development (OR = 0.23; 95% CI = 0.082–0.699; p = 0.009).  Conclusion. The hand grip development level and visual laterality are worse in children with speech (articulation) impairment and developmental deviations. These indicators of child development should be used as a guide in designing the national programs for developmental assessment and prevention in the child healthcare system.
Keywords: child; growth and development; motor activity; national health program; serbia; speech; speech disorders